First record of the Central Indo-Pacific reef coral Oulastrea crispata in the Mediterranean Sea - HOEKSEMA, B. W.; OCANA VICENTE, O. (Mediterranean Marine Science, 2014)
A live colony of a non-indigenous zooxanthellate scleractinian coral was found in shallow water at the west coast of Corsica, western Mediterranean. Its diameter of 6 cm suggests that it has already survived for some years. It was identified as Oulastrea crispata, a species native on near-shore coral reefs in the central Indo-Pacific with a high tolerance for low water temperatures at high latitudes. Based on its morphology it can be distinguished from other zooxanthellate colonial scleractinians in the Mediterranean. O. crispata has a reputation of being a successful colonizer because it is able to settle on a wide variety of substrata and because it utilizes various reproductive strategies as simultaneous hermaphrodite and producer of asexually derived planulae. Owing to its original distribution range in temperate and subtropical waters, it is likely that it will be able to meet a suitable temperature regime in the Mediterranean for further range expansion.